THE RANGE OF NEEDS SATISFIED BY THE USE OF URBAN LOGISTICS - Chłąd, Mateusz; Sobocinski, Maciej (Advanced Logistic Systems - Theory and Practice, 2016)
Urban areas are important centres of entrepreneurship and innovation. Transportation has a key meaning for the proper functioning of modern urban societies, which is struggling with problems related to economic activity. To reach their basic goals, cities are facing a task to encourage entrepreneurs to economic activity; one of the possible ways to achieve this task is to improve the conditions of freight transport. Solutions from urban logistics are pointed out as a practical way of improving the transport-logistic systems of modern cities, which struggle with unreasonable structure of freight, traffic congestion and undesirable influence of transport activities on their environment.